Unraveling the Complex Role of Zinc, Boron, Chromium, and Selenium in the Pathogenesis of Diabetes Mellitus: A Review - Jawad Musafer KN; Zulkeflee HA; Wan Nik WNFH; Ab Rahim SN; Tuan Ismail TS (Kulliyyah of Medicine, International Islamic University Malaysia, 2024)
Indexed by WOS/Scopus